Peningkatan Hasil Belajar Peserta Didik Kelas 2 Melalui Model Pembelajaran Discovery Learning - Yanti, Tri (Universitas Sebelas Maret, 2020)
The purpose of the research: To describe the enhancement of the students` study result during the online learning by using the learning model of the power point and the whatsapp group. In order be suitable to the education purpose in which to develop the students` individual talent and skill,so the students` psyche potenty couldbe actualized perfectly so it needs some methods that hoped to be the indicator achieving the teaching and learning activity to achieve the desired purpose. Besides the method is very important unsure and can`t be lost in the education in achieving the desired purpose. The purpose of the enhancement will be achieved if there are students` participation and their parents` supports. Especially in the pandemicrecently. With students` activation ,it will create the most desireh learning result.